TEACHING QUEUING CULTURE IN EARLY CHILDHOOD - Daviq Chairilsyah (Jurnal Educhild : Pendidikan dan Sosial, 2019)
The culture of queuing or waiting turn is a simple behaviour that is sometimes forgotten by adults.Behaviour in queuing or waiting their turn is strongly believed and implemented by people in many developedcountries such as America and Europe. However, in Indonesia there are still seen adults who deliberatelyand do not want to queue or wait their turn for various reasons. In fact, it will trigger social conflicts in thecommunity. Therefore, inculcation of queuing culture needs to be taught and believed by individuals from anearly age, so that this queued behaviour can be well embedded and automatically becomes a behaviour thatwill be displayed in everyday life. This paper is presented using the literature study method. Literature studyor what is known as literature review is a description of the theory, findings, and other research materials thatare used as a basis for research activities in preparing the framework of the problem formulation. In thispaper, we will describe the role of parents and teachers is specific and concrete in educating children to havequeuing behaviour in waiting their turn.